Determinant for Implementation of Early Breasting In PMB of Banjarmasin City In 2019 - Darmayanti wulandatika; Bening Prawita Sari; Pratiwi Puji Lestari (UrbanGreen, 2019)
Early Breastfeeding Initiation (IMD) is a process of allowing babies with their own instincts to breastfeed as soon as in the first hour after birth, together with contact between baby's skin and mother's skin (MOH RI, 2008). This study is an analytical study with a cross-sectional approach. Both the independent variable and the dependent variable according to circumstances or status at the time of observation. The researcher looks for the relationship between the independent variable and the dependent variable by taking a quick measurement. The results of this study were that respondents with good IMD implementation amounted to 61.7% and those who did poorly amounted to 38.3%. These results indicate that statistically there is no relationship between maternal education with actions in implementing IMD, and there is a relationship between knowledge and attitudes of mothers with the implementation of IMD